2023
DOI: 10.3389/fendo.2023.1160936
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of intravenous monoclonal antibodies in patients with moderate-to-severe active Graves’ophthalmopathy: a systematic review and meta-analysis

Abstract: BackgroundsThe effects of various treatments on Graves’ ophthalmopathy (GO) have been studied. As monoclonal antibodies (mAbs) have been proposed for the treatment of moderate to severe GO, direct comparisons between different mAbs are lacking.We therefore conducted this meta-analysis to objectively compare the efficacy and safety of intravenous mAbs.MethodsTo identify eligible trials, references published before September 2022 were electronically searched in PubMed, Web of Science, Pubmed, Embase,Cochrane Lib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 84 publications
0
5
0
1
Order By: Relevance
“…33,44–49 While the sole randomized controlled trial (RCT) available showed that the reduction in proptosis wasn´t statistically significant at the 40-week follow-up, 44 a recent meta-analysis suggests that TCZ may be the best treatment for proptosis reduction, followed by Teprotumumab and Rituximab. 62 Importantly, considering the 146 patients in which a possible recurrence is described, only 12 presented relapsing signs after treatment discontinuation, 30,32,39,49,54,55,58 which equals an overall relapsing rate of 8.2%, not far from the 7.4% described by Pérez-Moreiras et al 49 in his retrospective analysis of 54 patients.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…33,44–49 While the sole randomized controlled trial (RCT) available showed that the reduction in proptosis wasn´t statistically significant at the 40-week follow-up, 44 a recent meta-analysis suggests that TCZ may be the best treatment for proptosis reduction, followed by Teprotumumab and Rituximab. 62 Importantly, considering the 146 patients in which a possible recurrence is described, only 12 presented relapsing signs after treatment discontinuation, 30,32,39,49,54,55,58 which equals an overall relapsing rate of 8.2%, not far from the 7.4% described by Pérez-Moreiras et al 49 in his retrospective analysis of 54 patients.…”
Section: Resultsmentioning
confidence: 88%
“…Moreover, in the study by Pampín-Sánchez et al, 55 diplopia resolution was only observed in 3 of the 8 affected patients. Hu et al 62 , considering their recent meta-analysis, suggested that TCZ was not optimal for diplopia improvement.…”
Section: Resultsmentioning
confidence: 99%
“…Diplopia persisted in fewer patients (25%, p = 0.250) after TCZ treatment [ 112 ]. A meta-analysis published in 2023, which analyzed 12 trials with 488 patients, confirmed the high treatment response rate of TCZ, including proptosis reduction (with a better outcome than TPT) [ 113 ]. An ongoing multicenter trial aims to evaluate the efficacy of TED treatment with intravenous TCZ compared to IVGCs (EudraCT number: 2018-002790-22, (accessed on 1 November 2023) identifier: NCT04876534).…”
Section: Potential and Current Drug Targetsmentioning
confidence: 98%
“…To date, there are no studies on the efficacy of this agent in the treatment of TED. Tocilizumab (TCZ) [113] Anti-IL-6R MAB A total of 12 trials with 448 patients were included Metaanalysis TCZ was most likely to be the best treatment in terms of response and proptosis reduction, followed by TMB and RTX. TMB was most likely to be the best treatment in terms of improving diplopia, followed by TCZ and RTX.…”
Section: Atx-gd-59 Restoration Of Tolerancementioning
confidence: 99%
“…We recently read an article published in Frontiers in endocrinology by Hu et al. The study compares the results of rituximab, tocilizumab, and teprotumumab in the treatment of moderate to severe GO, providing a nuanced analysis of their relative efficacy and safety profiles ( 1 ). We congratulate the authors on a very comprehensive work.…”
mentioning
confidence: 99%